Recombination and long-term relaxation of photoconductivity in р+–р–р– structures of CdxHg1–xTe (0.24 ≤ x ≤ 0.29) - Ismayilov, N.J.; Rajabli, A.A.; Musayev, M.A.; Abbasov, I.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
The paper presents the results of a study of the photoconductivity of р+–р–р– structures of CdxHg1–xTe (0.24 ≤ x ≤ 0.29) single crystals obtained by thermal diffusion of copper at T = 130°C. The long-term relaxation (LR) of photoconductivity with a duration of up to 10 ms in the presence of a thermal background of intensity Φ = 1016–1017 cm–2⋅s–1 is observed for the first time in narrow-gap materials in the T = 77–150 K range. Recombination, diffusion-drift processes in the sample are analyzed, which cause LR and spectral features of photoconductivity. The obtained structures are promising for the development of various highly sensitive IR detectors with an elevated operating temperature.